FROM THE HISTORY OF THE ORIGIN AND DEVELOPMENT OF NATIONAL GAMES (THE EXAMPLE OF UZBEK PEOPLE) - Ikhtiyor Jalilov (Scholars Digest Publishing, 2023)
In this article, the origin and development of the national games of the Uzbek people are highlighted based on available sources and historical-ethnographic literature.
Keywords: Uzbek, people, nation, national, games, performances, games, tradition, heritage, dexterous, agile.